Effect of feeding frequency on growth, feed utilization and nitrogen and phosphorus waste output of malabar grouper, Epinephelus malabaricus, reared in net pens - JI Wen-xiu; WANG Yan; LI Po-yu (浙江大学学报. 农业与生命科学版, 2011)
A net pen experiment was carried out to evaluate the effect of feeding frequency on growth, feed utilization and nitrogen and phosphorus waste output of malabar grouper, Epinephelus malabaricus. In the experiment, fish [initial body mass (137±1) g] were fed raw fish feed at 5 feeding frequencies, including 4 meals per day (4.00 meal·d-1), 2 meals per day (2.00 meal·d-1), 1 meal per day (1.00 meal·d-1), 1 meal every 2 days (0.50 meal·d-1) or 1 meal every 4 days (0.25 meal·d-1). The results indicated that feed intake (FI), mass gain, feed conversion ratio (FCR), nitrogen waste output (TNW) and phosphorus waste output (TPW) increased, while nitrogen retention efficiency (NRE) and phosphorus retention efficiency (PRE) decreased with the increase of feeding frequency from 0.25 meal·d-1 to 1.00 meal·d-1. However, no significant changes were found in FI, mass gain, FCR, NRE, PRE, TNW and TPW, when feeding frequency was further increased from 1.00 meal·d-1 to 4.00 meal·d-1. There were no significant differences in condition factor, hepatosomatic index and whole body composition among fish fed at different feeding frequencies. The results revealed that the suitable feeding frequency for malabar grouper fed raw fish feed should be at 1.00 meal·d-1. Fed at 1.00 meal·d-1 for 109 days, mass gain of malabar grouper was 253 g, and FCR was 1.1, and NRE was 22%, and PRE was 24%, and TNW was 108 g N·kg-1 fish production, and TPW was 24 g P·kg-1 fish production.